The dynamics green management, technology and social media in business, manufacturing and industries - Md Taib, Mohd Yazid; Mohamed Udin, Zulkifli; Abu Bakar, Azizi (2014)
Nowadays, numerous business and organizations are enthusiastically adopted green management and technology strategies to compete in the global business.In achieving the goal, it is necessary to access the implementations and practical ways of green management and technology in the industry so the best practices are identified.This paper describes the development of key dynamics, which will ameliorate the adoption, implementation and practical ways of green management and technology.In addition, high motivation among team members in the entire organization is necessary to the sustainability.This paper is discussing the interrelationship between the green management, philosophy, technology and social media as a communication tool.